Kajian Reflektif Teori Thorndike Dalam Konteks Representasi Matematis Berdasarkan Ideologi Utilitarian - Rila Septia Pratama Putri Rila; Tian Abdul Aziz (Griya Journal of Mathematics Education and Application, 2022)
Mathematical representation is the center of mathematics learning activities. Representations help students understand various forms of mathematical presentation. Strengthening mathematical representation in learning is based on learning theory, namely Thorndike Theory. American Educational Psychologist Edward L. Thorndike has a "Law of Effect" view which means that learning will be more successful if the student's response to a stimulus is followed by a sense of pleasure and satisfaction. Thorndike views learning as a stimulus-response formation process that determines the quality of learning outcomes. This research is a literature review with the aim of knowing what stimulates student representation, how teachers act so that students are able to create appropriate representations, and how students create appropriate representations. Various views on learning theory have emerged, one of which is utilitarian which views a good action as maximizing a sense of satisfaction and happiness. Representation in the formation of stimulus-response is intended for the success of learning mathematics that causes satisfaction. This paper attempts to shed the author's reflective thoughts on Thorndike's Theory in the context of mathematical representation based on Utilitarian ideology.